The insider's guide to winning education grants - Pawlicki, Dakota; James, Chase (San Francisco, CA : Jossey-Bass, 2013)
'Find, apply for, and win grant dollars for the classroom This accessible guide offers a proven, step-by-step process for researching, writing, applying for, and winning education grants. The book educates readers on the basics of grant writing, including what sources are the most reliable for securing education funding. It also serves as a practice tool, with worksheets, proposal templates, real-world examples, and advice from grant-winning teachers to help instill confidence about navigating this somewhat daunting process. Offers a proven formula for winning education grants in clear, step-by-step instructions Includes a wealth of handy tools, worksheets, templates, and teacher-tested advice Outlines the four main components of money-generating education grants Based on UNITE's celebrated'Grant Writing Teacher' Professional Development series The book's step-by-step process is filled with illustrative examples of successful grant proposals'--
Includes bibliographical references and index.
Keywords: Educational fund raising -- United States -- Handbooks, manuals, etc; Proposal writing in education -- United States -- Handbooks, manuals, etc; Federal aid to education -- United States -- Handbooks, manuals, etc; Government aid to education -- United States -- Handbooks, manuals, etc